Knit, Crochet, and Stitch for Child Rights and Social Justice: Practicing Craftivism in Early Childhood Education and Care Settings - Bjartveit, Carolyn; Henderson-Dekort, Emmie; DeCecco, Emma; Bagshaw Brooks, Alisha (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
Utilizing a duoethnography research methodology, postsecondary students and professors discussed how preschool children’s engagement in craftivism supported their understanding of homelessness. Media and picture books provoked conversations and increased the children’s awareness of social issues impacting marginalized youth who are silenced and othered. Third-wave feminist ideas related to craftivism and Miranda Fricker’s thinking on epistemic injustice provided a scholarly framework for the research. The study findings point to the importance of listening to children’s voices and honouring their right to actively explore social issues through play, dialogue, and craftivism.